A Descriptive Study On Speaking Teaching-Learning Process At The Second Year Of SMA N 2 Sukoharjo - Khomarudin, Mohamad (2012)
This research aims at describing the speaking teaching-learning process at the second year of SMA N 2 Sukoharjo. It describes the teaching-learning process that consists of the technique, material, media, and evalution implemented in speaking teaching-learning process at the second year of SMA N 2 Sukoharjo, problems faced by the teacher and students in learning speaking, and then the strategies used by the teacher to overcome the problems. The data are taken from event, informants, and documents. The technique of collecting data are conducting interview, observation, and analyzing document in speaking teaching-learning process. Based on the data analysis, it can be concluded that the techniques implemented by the teacher in teaching speaking are brainstorming, information gap, problem solving and decision making. The materials used in teaching speaking are taken from the government, student worksheet and the other sources, it's like from the other book. The media used in teaching speaking is printed material, but sometimes the teacher used electronic media. And the teacher evaluated the teaching speaking during the process of speaking teaching and learning in classroom of XI.Bahasa using question-answer. The researcher finds the problems faced by the learners, they are nervousness, pronunciation, grammar, and vocabulary. And the problems faced by the teacher are lack of motivation from students, lack of reading habit by the students, and the difficulty to operate the supporting media. Then the problem solving used by teacher are the teacher gives motivation to encourage students, teacher makes an easy question, teacher promotes the English lesson, and teacher gives the chances to ask anything about English lesson.